Pengaruh Daya Tarik Visual Area Tematik Terhadap Minat Berkunjung Kembali Wisatawan di Lippo Mall Puri - Aurellie, Carren; Rahmad, Muhammad; Haryono, Joko (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2098, 2026)
This study aims to analyze the influence of M Bloc Space’s attractiveness on Gen Z visitor satisfaction in urban tourism in South Jakarta. The research uses a quantitative method with descriptive and associative approaches. Data were collected through questionnaires distributed to 100 respondents who visited M Bloc Space. Data analysis was conducted using validity and reliability tests, Pearson correlation, coefficient of determination, simple linear regression, and t-test with SPSS 21. The results show that the attractiveness of M Bloc Space is categorized as very attractive with a mean score of 4.26, while visitor satisfaction is categorized as very satisfied with a mean score of 4.24. Pearson correlation analysis indicates a very strong and positive relationship between attractiveness and visitor satisfaction, with a coefficient of 0.915. The coefficient of determination shows that 83.7% of visitor satisfaction is influenced by attractiveness, while 16.3% is influenced by other factors. The t-test results indicate that attractiveness has a significant effect on visitor satisfaction. In conclusion, the attractiveness of M Bloc Space has a positive and significant impact on visitor satisfaction. It is recommended to improve amenities such as toilet cleanliness and adjust souvenir pricing to be more affordable.  Keywords : tourist attraction, visitor satisfaction, M Bloc Space, Gen z, urban tourism